2011
DOI: 10.1136/bmjqs.2008.028381
|View full text |Cite
|
Sign up to set email alerts
|

A human factors framework and study of the effect of nursing workload on patient safety and employee quality of working life

Abstract: Backgrounds Nursing workload is increasingly thought to contribute to both nurses’ quality of working life and quality/safety of care. Prior studies lack a coherent model for conceptualizing and measuring the effects of workload in health care. In contrast, we conceptualized a human factors model for workload specifying workload at three distinct levels of analysis and having multiple nurse and patient outcomes. Methods To test this model, we analyzed results from a cross-sectional survey of a volunteer samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
166
2
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(186 citation statements)
references
References 82 publications
7
166
2
11
Order By: Relevance
“…This affects the thinking process and concentration, and increases the number of errors. Holden et al (2011) showed that there is a significant positive correlation between mental workload and possibility of creating errors (Holden et al, 2011). In fact, human error is one of the major causes of occupational accidents (Wiegmann and Shappell, 2001;Young et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This affects the thinking process and concentration, and increases the number of errors. Holden et al (2011) showed that there is a significant positive correlation between mental workload and possibility of creating errors (Holden et al, 2011). In fact, human error is one of the major causes of occupational accidents (Wiegmann and Shappell, 2001;Young et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The high level of mental workload not only affects occupational accidents but also increases the prevalence of depression, occupational stress, and burnout. Furthermore, the high mental workload affects health and welfare of personnel as well as safety of patients (Holden et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per Berry and Curry (2012) unequivocal nursing overload negatively affects patient outcomes. There is a significant evidence indicating that improved nurse staffing and hours of work reduce medication errors (Holden et al, 2011). According to Thungjaroenku et al (2007) a proper nursing staffing can reduce patients' length of stay.…”
Section: Introductionmentioning
confidence: 99%
“…2B) Errors in administration of medication. Two studies focused on understaffing and medication errors [53] [56], reporting that heavy nursing workload, interruptions and being rushed increased the risk of adverse events in conjunction with the administration of medication. Several other studies found an association between understaffing and medication errors, even when this was not their focus [15] [17] [52].…”
Section: Thematic Analysismentioning
confidence: 99%